Mechanical and Physical Properties of Hybrid Cu-Graphite Composites Prepared via Powder Metallurgy Technique - Farouk M. Mahdi; Jawadat A. Eaqoob; Fouad R. Muhialdeen (Tikrit Journal of Engineering Sciences, 2017)
Copper -graphite composites are widely used in a great number of engineering applicationssuch as brushes, switches, sliding bearings, self-lubricating bearings, etc. due to their goodthermal and electrical conductivity and excellent tribological properties as compared with otherstructural materials. There are ongoing attempts in manufacturing copper composites with betterproperties to enhance their efficiency and increase their effective life. Present research aims to prepare hybrid 95wt.% copper –5wt.% graphite composites reinforced with yttria and tin particles by powder metallurgy technique and to study their effects on mechanical and physical properties of the prepared composites. Powder mixture was mixed by ball mill mixer at 100rpm for 120min with (5/1) balls to powder ratio. The powder mixture was cold pressed at 700MPa for 30sec, followed by sintering at 900 ?C for one hour. In the first stage, Yttria(Y2O3) was added with (2, 4, 6, 8, 10) wt% to pure copper (Cu) and to (95%Cu-5%Gr) matrices. Typical composite of this stage was ((95%Cu-5%Gr)-4%Y2O3. In the second stage, tin (Sn) was added with (2, 4, 6, 8, 10) wt% to pure copper and((95%Cu-5%Gr)-4%Y2O3 matrices. Typical composite of this stage was ((95%Cu-5%Gr)-4%Y2O3)-6%Sn. The results showed that hardness and true porosity of the composites increases with increasing yttria content. On the other hand both thermal and electrical conductivity of the composites decreases with increasing yttria content. It was also found that (95 wt.% Cu- 5 wt.% Gr) – Y2O3 composites have always lower wear rate than plain Cu-Y2O3 composites.